Exploring Institutional Factors Influencing Digital Assessment Adoption - Bahreini, Marzieh; Aslani, Farzad (Assessment and Practice in Educational Sciences, 2023)
This study aims to explore the institutional factors that influence the adoption of digital assessment practices in higher education institutions in Pakistan. A qualitative research design was employed to gain in-depth insights into institutional-level enablers and barriers to digital assessment adoption. Data were collected through semi-structured interviews with 22 participants, including faculty members, administrators, and educational technologists from various public and private universities across Pakistan. Participants were selected purposively based on their involvement in digital assessment planning or implementation. Interviews continued until theoretical saturation was achieved. All interviews were transcribed and analyzed using thematic analysis with the support of NVivo software, following an inductive coding process and Braun and Clarke’s six-step framework. Three overarching themes emerged from the data: Organizational Readiness, Pedagogical Perceptions and Practices, and Cultural and Contextual Influences. Within organizational readiness, participants cited infrastructural limitations, low digital literacy, unclear policies, and weak administrative support as key barriers. Pedagogical concerns included doubts about assessment fairness, limited compatibility with teaching philosophies, lack of faculty autonomy, and ineffective training. Cultural and contextual factors, such as hierarchical institutional culture, leadership indifference, and societal skepticism toward online exams, were found to shape attitudes and practices. Disciplinary variation and student engagement challenges further influenced the differential adoption of digital assessment across faculties. The adoption of digital assessment in Pakistani higher education institutions is shaped by a complex interplay of infrastructural, pedagogical, and cultural factors. Successful integration requires not only technological investment but also institutional reform, leadership engagement, and pedagogical alignment. Strategies that are context-sensitive, faculty-driven, and collaboratively implemented hold the greatest potential for sustainable transformation in assessment practices.